Pengaruh Penambahan Trehalosa dalam Pengencer Tris terhadap Kualitas Semen Cair Domba Garut (Ovis aries) - Herdis Herdis; Maman Surachman; Muhammad Rizal; Arief Boediono; Yulnawati Yulnawati (Fakultas Biologi | Universitas Jenderal Soedirman, 2006)
This study was aimed to examine the quality of chilled-cement of Garut ram which was diluted with Tris extender and various trehalose concentrations. Cement was collected from three mature rams using an artificial vagina once a week. After initial evaluation, the cement was divided into four parts and diluted with Tris extender only (control), Tris extender + 0.20% (TR0.2), Tris extender + 0.40% (TR0.4), and Tris extender + 0.60% (TR0.6) trehalosa respectively. The extended-cement was stored at 5oC. Parameters of chilled-cement quality examined were percentage of sperm motility, live sperm, and intact plasma membrane (IPM), which were evaluated every day for four days. The results showed that addition of trehalose did not significantly improved the percentage of sperm motility, live sperm, and IPM (P>0.05) of Garut ram sperm stored in refrigerator at 5oC for 4 days. In conclusion, the addition of trehalose does not enhance the quality of chilled-cement of Garut ram.